2023
DOI: 10.21067/jip.v13i1.8207
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Engagement in Digital Mind Mapping-Supported Collaborative Learning during the Post-Pandemic Era

Abstract: Previous research has demonstrated the effectiveness of digital mind-mapping in improving student learning outcomes, creativity, critical thinking skills, and motivation. However, past studies rarely focused on student engagement when exploring the implementation of collaborative digital mind mapping in higher education. This study explored student engagement in a digital mind-mapping-supported collaborative classroom. The study was qualitative descriptive in nature, involving twenty fourth-semester students f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…It also increases respect and understanding among students as they must formulate their thoughts before interacting with their peers and teachers. This finding is similar to those reported by Sari et al (2023), which revealed that 'students' emotional engagement in the language classroom could help them complete a task successfully.…”
Section: Telegram and Its Contribution To Learningsupporting
confidence: 90%
See 1 more Smart Citation
“…It also increases respect and understanding among students as they must formulate their thoughts before interacting with their peers and teachers. This finding is similar to those reported by Sari et al (2023), which revealed that 'students' emotional engagement in the language classroom could help them complete a task successfully.…”
Section: Telegram and Its Contribution To Learningsupporting
confidence: 90%
“…By assigning research tasks and instructional videos for students to watch, teachers can encourage student engagement with the material (Berg, 2020) and interactive course materials that students can use (Vlachopoulos & Makri, 2019). When students interact with interactive learning content and tasks, they retrieve prior knowledge, process new knowledge, and synthesize both to produce knowledge (Berg, 2020;Sari et al, 2023).…”
Section: Telegram For Interactionsmentioning
confidence: 99%